Optical and Structural Characterization of Bi2FexNbO7 Nanoparticles for Environmental Applications - Araujo Scharnberg, Allan Ramone; Carvalho de Loreto, Adrison; Kopp Alves, Annelise (Ital Publication, 2020)
Photocatalytic materials development is very important from an environmental perspective. They can be employed in clean energy production by hydrogen generation as well as in wastewater treatment by photocatalysis. One of the key subjects in this area is the advancement of materials with a low band gap, thus the catalyst can use the sunlight more efficiently. Based on this issue, this research aims to develop photocatalysts based on bismuth, niobium, and iron (Bi2FexNbO7), analyze the influence of iron concentration (x = 0, 0.8, 1, and 1.2) and characterize them through optical and structural analysis. The powder samples were synthetized by the sol-gel method. Band gap estimation was performed using UV-Vis analysis and the Kubelka-Munk method. The XRD technique was employed for phase determination and structural characterization. The catalyst with no iron (Bi2NbO7) presented a mix of three phases of reagents and a band gap of 3.14 eV. The iron addition promotes crystalline photocatalysts with high visible light absorption ability and a lower band gap, 2.09 eV. Further analysis must be performed. However, based on structural and optical proprieties, these materials can efficiently be employed both in wastewater treatment and hydrogen production.